(untitled) (Environment & Health, 2020)
The aim of the work was to study the features of lipid peroxidation in the organism of the animals under effectof electromagnetic radiation. Material and methods.The investigations were carried out under conditions of 4-month chronic experiment on outbred white rats which were divided into groups according to the effective intensity of 2000 V / m •hv, 4000 V / m •hv and 6000 V / m•hv. Results.An increase ofthe LPO processes in the blood and liver has been established.These changes were manifested depending on the level of electromagnetic radiation intensity and exposure time. Non-enzymatic stimulation of Fe2 + -dependent lipid peroxidation, increase of the enzymatic NADPH-induced accumulation of TBA-active products in rat liver homogenate, increase in the dynamics of spontaneous MDA accumulation in rat blood plasma and liver homogenate were revealed. Conclusions.Performed investigations show that the enhancement of lipid peroxidation processes is a mechanism of the manifestation of the hazardous effect of EMR, which makes it possible to develop oxidative stress and, as an indicator of intracellular disorders, can serve as a biomarker of adverse effects. The severity of activation of lipid peroxidation system allows us to consider this as a criterion for the assessment of the hazard of the electromagnetic factor.